Citizen Forum on Participatory Planning and Budgeting to Promote the Inclusive Village Governance - Rifai, Rifai; Taufiq, Muhammad; Hidayat, Rahmad; Sauki, Muhammad (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
After 23 years of reformation, one of the regulatory products that reflect the devolution and delegation of decentralized development management authority to the local government is Law No. 6/2014 on Villages which promises further community involvement, by placing the village as the centre of regional development and not only as an object of the national programs. This citizen forum facilitation was held in the context of expanding understanding of the substance of participatory planning and budgeting and the significance of community involvement in the village development management which was carried out during August 2021 in the Bajo Village, Soromandi District, Bima Regency, West Nusa Tenggara Province by involving dozens of people, especially women's groups, as participants. The main methods applied during this facilitation to discuss everything related to the prospects, constraints, and substantive needs of the program were in the form of lectures, brainstorming, practise, and mentoring. The group of women who participated on average emphasized that they were not citizens who had been involved and in the village planning-budgeting deliberations that had been held there. They have never experienced the atmosphere of regular civic forums such as the Musdes and the Musrenbangdes to discuss the draft of the RPJMDesa, the RKPDesa, and the APBDesa documents because there was no access and an opportunity to voice their collective needs to the Village Government. The activity output showed that there has been a seed of collective awareness from all participants to take a role in the planning-budgeting forums for the coming year and utilize them as a medium for channelling their aspirations, interests, or needs to the Village Government and the BPD. They were very aware of the various priority needs that must be fought for their articulation, both directly and through the intermediary of the Village Community Institution managers.